Examining Factors Affecting Labor Force Participation: Global Economic Analysis - Amin, Md. Ashraful; Md Amirul Islam; Abdul Kader Jelane; Umme Sumaia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Utilizing econometric modeling and data from thirty-three observations, the study investigates how important economic variables affect LFPR.GDP growth, the FDI ratio, inflation, and trade ratios are among the variables. The findings show a relationship between long-term fixed rate mortgages and foreign direct investment (FDI), but not between total lending. The effects of inflation and GDP growth are less evident. The study highlights the complexity of labor market behavior modeling while taking into account potential problems with econometric models, such as heteroscedasticity and autocorrelation. The results also significantly close knowledge gaps in the economic dynamics underlying labor force participation and provide policymakers with recommendations for improving the efficiency and inclusivity of the labor market. The analysis's conclusions show that all the various social, demographic, and economic factors that affect labor force dynamics must be taken into account when creating policy.